PENGELOLAAN AKREDITASI SEKOLAH DASAR (Studi Situs di SD Islam Hj. Isriati Ungaran) - SUKEMI, SUKEMI (2011)

(untitled)
The purposes of this research are to describe (1) Preparation of accreditation in Elementary School Islam Hj. Isriati Ungaran, (2) The implementation of accreditation in Elementary School Islam Hj. Isriati Ungaran, and (3) The condition after the implementation accreditation in Elementary School Islam Hj. Isriati Ungaran. This is qualitative research that conducted in Elementary School Islam Hj. Isriati Ungaran. Data collection techniques in this research used observation, interview and documentation. Technique of data analysis conducted with data collection, data reduction, data presentation, and conclusion. The validity of the data used credibility (internal validity), transferability (external validity), dependability (reliability), and conformability (objectivity). The results of the research are (1) Preparation of accreditation in Elementary School Islam Hj. Isriati Ungaran is consists of two stages that is administration and self evaluation of school. In preparation for school administration is to collect data on school conditions in accordance with the eight components of accreditation. Eight component of accreditation standards include: standards of content, competency standards, standards of educators and education personnel, facilities and infrastructure standards, management standards, financial standards, and assessment standards. Implementation of self-evaluation in the elementary schools Islam Hj. Isriati Ungaran begins with the formation of Self-Evaluation Team that is coordinated by the principal. And each member school to school self-evaluation based on their job. (2) In the implementation of accreditation consists of several stages that are by conducted self-evaluation of school. After performing self-evaluation, the school held a meeting with a team of assessors. Further implementation of the accreditation process is the schools provide physical evidence that is in school, such as facilities and infrastructure. Visitation is conducted by a team of assessors conducted to find the data required in the implementation of accreditation also to prove whether the data collected school is in conformity with the existing realities in the field or not. And the last stage is awaiting the results of BAN S/M. (3) Implementation of school accreditation is to bring changes to the school. These changes can be seen from the components accreditation in the school which consists of 8 components of accreditation. These changes can be written from the result of accreditation.